‘And this in thriving and prosperous Antrim!’: An Anglo-Irish landlord’s perspective on the Famine - Wesley Hutchinson (Revue Française de Civilisation Britannique)
The article is a study of a pamphlet published in 1847 by Alexander Shafto Adair, a landlord in Ballymena, Co. Antrim, and a Whig MP. In addition to being a valuable testimony as to the situation in one of the least affected areas of Ireland during the Great Famine, the pamphlet reveals the concerns of Irish landlords who were then being scapegoated by the English. If Adair concurs with a number of objectives of the Government, such as consolidation of the land and encouragement to the emigration of tenants, his initatives also aim at presenting Irish landlords in the best possible light in order to secure an understanding with London. Yet his blindness to the plight of the poor also participated in the creation of a resentful Irish diaspora that was to support the emerging nationalist movement.